Assessing the Exergy Costs of a 332-MW Pulverized Coal-Fired Boiler - Victor H. Rangel-Hernandez; Cesar Damian-Ascencio; Juan M. Belman-Flores; Alejandro Zaleta-Aguilar (Entropy, 2016)
In this paper, we analyze the exergy costs of a real large industrial boiler with the aim of improving efficiency. Specifically, the 350-MW front-fired, natural circulation, single reheat and balanced draft coal-fired boiler forms part of a 1050-MW conventional power plant located in Spain. We start with a diagram of the power plant, followed by a formulation of the exergy cost allocation problem to determine the exergy cost of the product of the boiler as a whole and the expenses of the individual components and energy streams. We also define a productive structure of the system. Furthermore, a proposal for including the exergy of radiation is provided in this study. Our results show that the unit exergy cost of the product of the boiler goes from 2.352 to 2.5, and that the maximum values are located in the ancillary electrical devices, such as induced-draft fans and coil heaters. Finally, radiation does not have an effect on the electricity cost, but affects at least 30% of the unit exergy cost of the boiler’s product.